32.3k views
4 votes
Plllllllzzzzzzzzzzzz helllppppppp

Plllllllzzzzzzzzzzzz helllppppppp-example-1

2 Answers

3 votes

Answer:

the Answer is B.

8x-(-4)x+6

X=1/2

Y=-4 *1/2

y=-2

The final aswer is (1/2, -2)

Explanation:

User Duygu
by
5.3k points
5 votes

All you have to do is substitute the y value into the second equation.

8x - (-4x) = 6; double negative turns it to a positive

8x + 4x = 6; combine like terms

12x = 6; divide both sides by 12

x = 1/2 then substitute this x value into the second equation again

8(1/2) - y = 6; multiply

4 - y = 6; subtract 4 from both sides

-y = 2; multiply both sides by a negative to make y positive again

y = -2

The solution is (1/2, -2)

User Muhammad Hamed
by
5.0k points